An objective assessment of halitosis in children with adenoid vegetation during pre- and post-operative period - Dinc, Mehmet Emre; Altundag, Aytug; Dizdar, Denizhan; Avincsal, Mehmet Ozgur; Sahin, Ethem; Ulusoy, Seckin; Paltura, Ceki (International journal of pediatric otorhinolaryngology, 2016)
Although most specialists in otorhinolaryngology and pediatrics find halitosis to be a common problem in children with adenoid hypertrophy, there are no objective data on this topic in the literature. Whether adenoid hypertrophy is a risk factor for halitosis or whether halitosis is a sign of adenoid hypertrophy remains unclear. Thus, the aim of this study was to investigate whether children diagnosed with adenoid hypertrophy have a higher probability of halitosis than do children in the normal population and whether adenoidectomy can decrease oral malodor. Forty children with adenoid hypertrophy and 40 healthy subjects aged 5–15 years were included in the study. The children with adenoid hypertrophy underwent adenoidectomy operations and were followed for 3 months. We measured volatile sulfur compounds (VSCs), hydrogen sulfide (H2S), methyl mercaptan (CH3SH), and dimethyl sulfide (CH3)2S using an objective method, a portable gas chromatograph (OralChroma; AbiMedical, Osaka, Japan). The mean CH3SH and (CH3)2S levels were significantly different (p < 0.05) between the adenoid hypertrophy group and the controls. The H2S, CH3SH, and (CH3)2S levels in the third postoperative month were significantly lower (p < 0.05) than those in the preoperative period, and there was no significant difference postoperatively between the patients with adenoid hypertrophy and controls. There was a positive correlation between age and VSC levels, and CH3SH levels were significantly higher in patients with ventilation tube insertion, rather than just adenoidectomy. There was a statistically significant association between halitosis and adenoid hypertrophy, and a significant improvement in halitosis was obtained following adenoidectomy. The present study provides an association between halitosis and adenoid hypertrophy. If there is no other oral pathology causing halitosis, halitosis can be a sign of adenoid hypertrophy in children.